Reforma postępowania z nieletnimi. Uwagi ogólne na temat materialnoprawnych rozwiązań ustawy z 26.X.1982 r. o postępowaniu w sprawach nieletnich: [A reform in treating juveniles] (Studia Prawnicze / The Legal Studies, 1984)
The article analyzes material and legal principles of treating juveniles on the basis of the solutions of the Polish law on procedure in juvenile cases of October 26, 1982. It shortly presents the evolution .of treatment of juveniles, considers such notions as "juvenile", "demoralization", "punishable act", "responsibility of a juvenile". The article also analyzes a catalogue of measures which may be applied towards juveniles in the light of the new law.The evaluation of the model of treatment of juveniles accepted by the laW is rather critical; first of all, the author points to too little respect for the rights of children and youth.The author thinks that treatment of juveniles should include the model of "rights of juveniles" and the concept "a child in danger".